Évolution des systèmes fonciers au Mali : Cas du Bassin Cotonnier de Mali Sud Zone Office du Niger et Région CMDT de Koutiala. - Camara, Bakary (CODESRIA (Conseil pour le Developpement de la Recherche Economique et Sociale en Afrique), 2015)
The book highlights, the gradual change in the status of the land and relationships with land in Mali in general and in the Niger river basin in particular. It is suggested that despite these inevitable transformations, institutional reforms need to be measured. They must be done in a prudent, methodical way with patience and determination while taking into account certain realities to mitigate its impact on the rural populations.